1881 Ill. Pub. Laws 71 §3 - (:unkn) unknown (General Publisher, 1881)
Required all dealers to keep a registration of all deadly weapons sold or given away, including any slung-shot, metallic knuckles, pistol, revolver, derringer, Bowie knife, dirk, or other deadly weapon.
--
Keywords: REGISTRATION